The Authorized Economic Operator in the European Union - Wolffgang, Hans-Michael (2007)
Provides an overview of the following subjects: the basic concept underlying the 'Authorized Economic Operator' (AEO) viz. legal foundations; different classes of AEO authorization; substantive and procedural certification; substantive and procedural certification criteria, issuing procedure; advantages of AEO status; and, finally, the revocation of AEO certification.